Team Turnarounds : A Playbook for Transforming Underperforming Teams - Frontiera, Joe and Leidl, Daniel (San Francisco Jossey-Bass, 2012)
How any manager can turn a struggling team into business champs In today's uncertain economic environment, teams are asked to do more with less. With resources stretched thin, turning around a struggling team has never been harder, and managers must work to identify and maximize whatever potential strengths a team already has. As sports fans already know, behind every great underdog story is a leader who roots out the competitive advantage that will propel the team to victory. In Team Turnarounds, Joe Frontiera and Dan Leidl share how this fine art of the turnaround really.
Include Index and Notes
Keywords: Management -- Organization -- Teams in the workplace